In The Spotlight: Understanding Healthcare Privatization’s Effects On Nursing Workforce And Care Quality – A Systematic Review In Saudi Arabia (Journal of Namibian Studies : History Politics Culture, 2023)
Background: This systematic review delves into the repercussions of healthcare privatization on the nursing workforce and care quality in Saudi Arabia (KSA). The backdrop is set against the backdrop of significant healthcare system changes in KSA, notably the shift towards privatization. With a particular focus on nursing, the study recognizes the crucial role nurses play in maintaining high standards of care and ensuring patient safety. Objective: The study aims to assess the impact of healthcare privatization on the standard of care in Saudi Arabia, with a specific focus on nursing practices and the broader healthcare environment. Key objectives include evaluating employment patterns, job satisfaction, and professional autonomy of the nursing workforce, as well as scrutinizing the impact of privatization on quality of care standards, patient outcomes, and satisfaction levels.Method: Adhering to the Preferred Reporting Items for Systematic Reviews (PRISMA) standards, the study conducts a thorough search of databases, including Google Scholar, Research Gate, and PsycINFO, covering the years 2019-2023. The systematic review criteria include specific inclusion and exclusion criteria to ensure the selection of pertinent research studies. The quality of the literature is assessed using the Joanna Briggs Institute Critical Appraisal Checklist.Findings: The synthesized findings from the selected studies highlight the complex and multifaceted nature of healthcare reform and privatization in KSA. Key themes emerge, including the impact on nursing management and workforce dynamics, assessment of healthcare systems, the role of executive nurse leaders, and the significance of education and training in preparing nurses for the evolving healthcare landscape.Conclusion: The collective body of research contributes to a comprehensive understanding of the opportunities and challenges associated with healthcare reform and privatization in KSA. It underscores the need for a coordinated and holistic approach to address systemic issues, ensuring equitable, accessible, and high-quality healthcare services for all segments of the population.